Evaluation of biofilm formation on acrylic resin surfaces coated with silicon dioxide: an in situ study - Silva, Rossano Vinícius Dala Rosa (2022)
Biofilm on acrylic resin dental prostheses may cause gingival inflammation. This study evaluated the influence of a silicon dioxide coating layer applied onto acrylic resin on the adhesion of microorganisms. Blocks (5 x 5 x 3 mm) of acrylic resin were evaluated for surface roughness and divided into two groups: control (CG) and coated with silicon dioxide (LG group). The specimens were evaluated by scanning electron microscopy (n = 1) and by contact angle analysis (n = 3). For the in situ study, 20 volunteers wore acrylic palatal devices containing three samples from each group (n = 60) for 2 days. The biofilm formed was quantified by metabolic activity and total biomass using the crystal violet assay. The results were subjected to Bartlett’s normality test and Gamma model with random effect for the response variable (α = 5%). The mean contact angle of the coated group was significantly lower than that of the uncoated group (p < 0.05). The metabolic activity of microorganisms in the biofilm on the blocks treated with coating was significantly lower than that of control blocks (p = 0.02). Regarding the amount of extracellular matrix produced by the microorganisms, there was no difference between the CG and LG group (p = 0.05). The application of a silicon dioxide coating on acrylic resin reduced the activity of the polymicrobial biofilm formed in situ. This coating may be advantageous for patients with conventional complete dentures or implants made of acrylic resin and who have motor difficulties that prevent them from cleaning their prostheses properly.